2004
DOI: 10.1152/ajplung.00004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation with moderate tidal volumes synergistically increases lung cytokine response to systemic endotoxin

Abstract: Previous animal studies have identified a role for activation of innate immunity in the pathogenesis of ventilator-associated lung injury. These studies have used large tidal volume ventilation to study the effect of alveolar overdistension on induction of inflammatory pathways. We hypothesized an alternative mechanism for the pathogenesis of lung injury in which moderate tidal volume ventilation does not independently cause clinical inflammation but rather interacts with innate immune activation by bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 39 publications
14
136
1
7
Order By: Relevance
“…Numerous experimental models of VILI have demonstrated additive or synergistic effects of bacterial products with mechanical ventilation on the development or exacerbation of lung injury [44][45][46][47][48]. Mechanical ventilation using moderate tidal volumes in mice enhanced lipopolysaccharide (LPS)-induced expression of TNF-α, IL-8, growth-related protein-α and monocyte chemoattractant protein (MCP)-1 [44].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…Numerous experimental models of VILI have demonstrated additive or synergistic effects of bacterial products with mechanical ventilation on the development or exacerbation of lung injury [44][45][46][47][48]. Mechanical ventilation using moderate tidal volumes in mice enhanced lipopolysaccharide (LPS)-induced expression of TNF-α, IL-8, growth-related protein-α and monocyte chemoattractant protein (MCP)-1 [44].…”
Section: Epithelial Cell Responses To Mechanical Stretchmentioning
confidence: 99%
“…Large tidal volumes (V T ) contribute to and worsen the acute respiratory distress syndrome (ARDS) in Intensive Care Unit (ICU) patients after hours or days of ventilation [1][2][3][4][5][6][7][8] . Recent studies suggest intraoperative ventilation settings affect postoperative pulmonary outcomes 1,[9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being temporally progressive, (21) this cytokine synthesis is potentiated by concomitant factors, such as systemic endotoxins and hyperoxia. (22,23) …”
Section: From Volutrauma To Biotraumamentioning
confidence: 99%
“…In addition to being temporally progressive, (21) this cytokine synthesis is potentiated by concomitant factors, such as systemic endotoxins and hyperoxia. (22,23) Based on the induction of a proinflammatory response in the lung epithelium associated with an alteration in permeability in the local endothelium, (14,24) some authors have suggested that there is decompartmentalization of…”
Section: From Volutrauma To Biotraumamentioning
confidence: 99%